2012
DOI: 10.3168/jds.2012-5489
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk contains microRNA and messenger RNA that are stable under degradative conditions

Abstract: We previously reported that microRNA (miRNA) is present in human breast milk. Recently, other groups have reported that bovine milk also contains miRNA; however, these reports are few. We therefore investigated bovine milk miRNA using microarray and quantitative PCR analyses to identify the differences between colostrum and mature milk. The RNA concentration in a colostrum whey fraction was higher than that in a mature milk whey fraction. In total, 102 miRNA were detected in bovine milk by microarray analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
423
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(442 citation statements)
references
References 42 publications
19
423
0
Order By: Relevance
“…Similarly, mEVs from bovine milk were isolated and characterized [13]. Our group demonstrated that bovine mEV contains mRNA and miRNA [14]; thus, mEVs may deliver these RNAs to recipient cells [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mEVs from bovine milk were isolated and characterized [13]. Our group demonstrated that bovine mEV contains mRNA and miRNA [14]; thus, mEVs may deliver these RNAs to recipient cells [15]. …”
Section: Introductionmentioning
confidence: 99%
“…While the majority of microRNAs are found and mediate their regulatory effects on gene expression intracellularly, a number of microRNAs are also present in the extracellular milieu and in various biological fluids of the human body, such as maternal milk [34][35][36][37][38], saliva [39,40], urine [41], nasal secretions [42,43], sperm [44] and plasma [45][46][47][48], and may represent interesting biomarkers of diseases [49,50].…”
Section: Extracellular Micrornas In the Circulationmentioning
confidence: 99%
“…Milk was collected from 24 multiparous cows at approximately 150 d in milk with diethylpyrocarbonate (DEPC)-treated tubes, stored at −20 °C immediately after collection, transferred to the laboratory within 2 h, and stored at −80 °C until further use. Milk pre-preparation procedures were performed according to Izumi et al (2012)'s protocol with some modifications. Briefly, samples were centrifuged twice (1200×g, 4 °C, 10 min), syringed into the middle defatted layer under RNase-free conditions, and dispensed into 1 ml aliquots per tube.…”
Section: Milk Sample Collection and Preparationmentioning
confidence: 99%
“…In the studies describing RNA extraction from cell-free fluids, such as milk whey, two alternative RNA extraction methods have already been performed, i.e. the phenol-based technique (Chen et al, 2010) and column-based approach (Trizol followed by cleanup using the modified RNeasy, miRNeasy or mirVana kit) (Izumi et al, 2012). Despite some discrepancies between these two isolation methods in other body fluid samples (McAlexander et al, 2013;Moret et al, 2013;Duy et al, 2015), none of these studies compared and evaluated the quantity and quality of the isolated miRNAs from milk using these two methods.…”
Section: Introductionmentioning
confidence: 99%